Digital sensitivity. The human being, artificial intelligence (AI), and new technologies - Aveni, Alessandro (Revista JRG de Estudos Acadêmicos, 2026)
Contemporary debates on artificial intelligence and human–machine interaction largely interpret technological development through functionalist and computational frameworks. Within these paradigms, cognition is treated as information processing and digital augmentation as the optimization or extension of pre-existing human faculties. Perception, in particular, is assumed to be a stable biological substrate that technology can enhance without fundamentally altering. Prevailing accounts rarely address how digital infrastructures reorganize the conditions under which reality becomes perceptible, meaningful, and actionable. By focusing on efficiency, performance, and “human-centric innovation” (as in the rhetoric surrounding Industry 5.0), current models risk obscuring the socio-historical and political mediation of sensitivity. This article introduces the concept of digital sensitivity to reconceptualize perception as a situated and historically mediated mode of world-disclosure rather than a discrete sensory function. The paper argues that the progressive integration of AI systems, distributed sensing networks, and digital platforms amounts to the emergence of a virtual artificial sense—an infrastructural layer of mediation that precedes and orients individual awareness. This development does not simply extend biological capacities; it transforms the structure of subjectivity and redefines how humans orient themselves within the world. The human–machine relation must therefore be understood as a process of co-constitution rather than augmentation. Reframing digital technologies as ontological mediators rather than neutral instruments has significant consequences for debates on agency, responsibility, and governance. Recognizing this shift allows us to move beyond polarized narratives of technological optimism or dystopia and toward a deeper reflection on how digitally saturated environments reshape human existence.